Analysis of Human Resource Recruitment in an Islamic Perspective - Appelletti Chiara; Forni Marina; Vantaggiato Gioia (Yayasan Adra Karima Hubbi, 2023)
This writing examines employee recruitment and Islamic views on recruitment that occurs in organizations. The purpose of this writing is to find out how recruitment is implemented in general and from an Islamic perspective in an organization. This writing is a literature review in which data is obtained from books, journals and related articles that explain recruitment. The results of this paper indicate that the principle of justice is needed in carrying out recruitment so that no party feels disadvantaged and abused in order to get qualified employees to help realize organizational goals.